Marine Algal Polyphenols as Skin Protective Agents: Current Status and Future Prospectives - H.H.A.C.K. Jayawardhana; Thilina U. Jayawardena; K.K.A. Sanjeewa; N.M. Liyanage; D.P. Nagahawatta; Hyo-Geun Lee; Jae-Il Kim; You-Jin Jeon (Marine Drugs, 2023)
The skin is the outermost anatomical barrier, which plays a vital role in the maintenance of internal homeostasis and protection against physical, chemical, and biological detractors. Direct contact with various stimuli leads to several physiological changes that are ultimately important for the growth of the cosmetic industry. Due to the consequences of using synthetic compounds in skincare and cosmeceutical-related industries, the pharmaceutical and scientific communities have recently shifted their focus to natural ingredients. The nutrient-rich value of algae, which are some of the most interesting organisms in marine ecosystems, has attracted attention. Secondary metabolites isolated from seaweeds are potential candidates for a wide range of economic applications, including food, pharmaceuticals, and cosmetics. An increasing number of studies have focused on polyphenol compounds owing to their promising biological activities against oxidation, inflammation, allergies, cancers, melanogenesis, aging, and wrinkles. This review summarizes the potential evidence of the beneficial properties and future perspectives of using marine macroalgae-derived polyphenolic compounds for advancing the cosmetic industry.